2021
DOI: 10.3389/fonc.2021.618485
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Treatment Regimens for Recurrent Cervical Cancer

Abstract: ObjectiveThe selection of individualized treatment for recurrent cervical cancer is challenging. This study aimed to investigate the impact of various therapies on survival outcomes after recurrence.MethodsEligible patients were diagnosed with recurrent cervical cancer between March 2012 and April 2018. Postrecurrence progression-free survival (PFS) and overall survival (OS) were investigated in the whole cohort and in subgroups, categorized by recurrence site and prior radiotherapy history, using a multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…But only 25% of the enrolled patients received adjuvant RT, and the proportion of patients undergoing re-irradiation was unclear in their study [4]. In addition, Li Lei et al found the salvage RT led to the best OS for recurrent cervical cancer within the pelvic cavity compared with other therapies [24].…”
Section: Discussionmentioning
confidence: 96%
“…But only 25% of the enrolled patients received adjuvant RT, and the proportion of patients undergoing re-irradiation was unclear in their study [4]. In addition, Li Lei et al found the salvage RT led to the best OS for recurrent cervical cancer within the pelvic cavity compared with other therapies [24].…”
Section: Discussionmentioning
confidence: 96%
“…Although surgeries such as pelvic exenteration are also treatment options for patients with cervical cancer who experience central pelvic relapse without pelvic wall involvement or extrapelvic spread, RT has its own advantages (most notably fewer complications). Pelvic exenteration is usually considered the only curative therapeutic approach, but it is associated with high surgery-related morbidity and mortality rates [19]; the survival rate is less than 50%, while mortality is nearly 5% [12,20]. Other surgical methods such as laterally extended pelvic/endopelvic resection carry certain risks of injury to the nerve, bladder, or rectum, leading to impaired urination and defecation.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of treatment for vaginal recurrence of cervical cancer remained challenging and highly individualized. Surgical therapy was beneficial for patients with vaginal recurrence, particularly for patients without RT history ( 9 ). However, the quality of life might be strongly affected because of the shortened length of vagina ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…The optimal salvage treatment regimen includes salvage radiotherapy (RT), chemotherapy, and reoperation such as pelvic exenteration depending on the primary treatment, type of recurrence, and associated comorbidities. RT with or without concurrent chemotherapy as salvage treatment seems to present promising treatment outcomes and tolerable toxicities (7)(8)(9). Several studies have proved that salvage RT can achieve better survival outcomes (8,10), especially when using brachytherapy (BT) for re-irradiation due to its conformal dose distribution (11,12).…”
Section: Introductionmentioning
confidence: 99%